1995
DOI: 10.1002/cne.903600203
|View full text |Cite
|
Sign up to set email alerts
|

Organization of projections from the medial nucleus of the amygdala: A PHAL study in the rat

Abstract: The organization of axonal projections from the four recognized parts of the medial amygdalar nucleus (MEA) were characterized with the Phaesolus vulgaris leucoagglutinin (PHAL) method in male rats. The results indicate that the MEA consists of two major divisions, ventral and dorsal, and that the former may also consist of rostral and caudal regions. As a whole, the MEA generates centrifugal projections to several parts of the accessory and main olfactory sensory pathways, and projections to a) several parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

58
526
5
10

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 709 publications
(601 citation statements)
references
References 120 publications
(191 reference statements)
58
526
5
10
Order By: Relevance
“…Our results, and those of others using cat odor, are consistent with the hypothesis that one of the major recipients of accessory olfactory projections, the "vomeronasal" medial amygdala, is also necessary for the behavioral and neuroendocrine responses induced by predator odor exposures. Although the medial amygdala is not reported to project directly to many, if any, of the effector/motor centers controlling behavioral, autonomic, and neuroendocrine responses (Canteras et al, 1995), it nevertheless projects to many regions such as the anterior bed nucleus of the stria terminalis, medial preoptic region, and a number of hypothalamic nuclei (dorsomedial, ventromedial, and premammillary divisions), that have those characteristics. Current anatomico-functional studies are under way to precisely define the input-output relationships of the medial amygdala with a specific focus on the vomeronasal subdivisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results, and those of others using cat odor, are consistent with the hypothesis that one of the major recipients of accessory olfactory projections, the "vomeronasal" medial amygdala, is also necessary for the behavioral and neuroendocrine responses induced by predator odor exposures. Although the medial amygdala is not reported to project directly to many, if any, of the effector/motor centers controlling behavioral, autonomic, and neuroendocrine responses (Canteras et al, 1995), it nevertheless projects to many regions such as the anterior bed nucleus of the stria terminalis, medial preoptic region, and a number of hypothalamic nuclei (dorsomedial, ventromedial, and premammillary divisions), that have those characteristics. Current anatomico-functional studies are under way to precisely define the input-output relationships of the medial amygdala with a specific focus on the vomeronasal subdivisions.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also associated relatively specifically the medial amygdaloid nucleus in defensive behavioral responses induced by cat or cat odor, or TMT exposures Li et al, 2004;Muller and Fendt, 2006). Given the emerging circuits controlling a variety of predator-induced defensive responses, we targeted the medial amygdaloid nucleus in our studies of the effects of ferret odors due to its well-known reception of odor information from a number of main and accessory olfactory regions, and its putative position to relay this information to regions controlling different effector response systems (Canteras et al, 1995). …”
Section: Brain Regions Mediating Acute Ferret Odor-induced Stress Resmentioning
confidence: 99%
“…In addition, we recently reported that fear-potentiated startle is also blocked by infusion of the AMPA receptor antagonist NBQX into the MeA (Walker et al, 2005). It is unclear how the MeA influences fear-potentiated startle as it does not project directly to the startle reflex circuit, the dSC/DpMe, or the CeA (Canteras et al, 1995). However, the MeA does have heavy projections to the ventromedial nucleus of the hypothalamus (VMH), and this pathway was found to contain SP (Canteras et al, 1994(Canteras et al, , 1995Han et al, 1996;Shaikh et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear how the MeA influences fear-potentiated startle as it does not project directly to the startle reflex circuit, the dSC/DpMe, or the CeA (Canteras et al, 1995). However, the MeA does have heavy projections to the ventromedial nucleus of the hypothalamus (VMH), and this pathway was found to contain SP (Canteras et al, 1994(Canteras et al, , 1995Han et al, 1996;Shaikh et al, 1993). Lesions of the VMH have been shown to disrupt other affective behaviors (Colpaert and Wiepkema, 1976;de Oliveira et al, 1997;Dielenberg et al, 2001;Han et al, 1996;Sudakov, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Canteras (2002) proposed that a medial hypothalamic defensive system (MHZ) mediates stimulus activation of the defense response elicited by a psychological threat stimulus, a predator. The MHZ initially integrates information relayed from the septohippocampal system with projections from several amygdala sites that receive or integrate information about threat stimuli (Canteras, et al, 1995). In turn, the MHZ relays the information upstream, via the thalamus, to the cortex , and downstream, through descending projections to brain stem regions, particularly the PAG (Canteras, et al, 1997;Canteras and Goto, 1999;.…”
Section: Introductionmentioning
confidence: 99%